The response of mesophyll conductance to short-term variation in CO2 in the C4 plants Setaria viridis and Zea mays - Ubierna, Nerea (Journal of experimental botany, 2018)
Mesophyll conductance (gm) limits rates of C3 photosynthesis but little is known about its role in C4 photosynthesis. If gm were to limit C4 photosynthesis, it would likely be at low CO2 concentrations (pCO2). However, data on C4-gm across ranges of pCO2 are scarce. We describe the response of C4-gm to short-term variation in pCO2, at three temperatures in Setaria viridis, and at 25 °C in Zea mays. Additionally, we quantified the effect of finite gm calculations of leakiness (ϕ) and the potential limitations to photosynthesis imposed by stomata, mesophyll, and carbonic anhydrase (CA) across pCO2. In both species, gm increased with decreasing pCO2. Including a finite gm resulted in either no change or increased ϕ compared with values calculated with infinite gm depending on whether the observed 13C discrimination was high (Setaria) or low (Zea). Post-transitional regulation of the maximal PEP carboxylation rate and PEP regeneration limitation could influence estimates of gm and ϕ. At pCO2 below ambient, the photosynthetic rate was limited by CO2 availability. In this case, the limitation imposed by the mesophyll was similar or slightly lower than stomata limitation. At very low pCO2, CA further constrained photosynthesis. High gm could increase CO2 assimilation at low pCO2 and improve photosynthetic efficiency under situations when CO2 is limited, such as drought